The Meyerbeer libretti Italian Operas 2, Emma di Reburgo, Margherita d'Anjou - Meyerbeer, Giacomo; Arsenty, Richard; Letellier, Robert Ignatius (Cambridge Scholars Publishing, 2008)
Giacomo Meyerbeer, one of the most important and influential opera composers of the nineteenth century, enjoyed a fame during his lifetime unrivalled by any of his contemporaries. This eleven volume set provides in one collection all the operatic texts set by Meyerbeer in his career. The texts are offered in the most complete versions ever made available. Each libretto is translated into modern English by Richard Arsenty; and each work is introduced by Robert Letellier. In this comprehensiv...
Keywords: Meyerbeer, Giacomo, : 1791-1864 : Emma di Resburgo; Meyerbeer, Giacomo, : 1791-1864 : Margherita d'Anjou; Operas : Librettos